(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the change in management capacity of head nurses at hospitals and medical centers with beds in Tuyen Quang province after capacity building and supervision training courses. Method: The study used a pre-post training comparison method on 89 head nurses at 14 hospitals and medical centers with inpatient beds in Tuyen Quang province from November to December 2024. Results: 8/11 criteria on management capacity, 10/13 criteria on human resource management capacity, 7/8 criteria on thinking capacity, 12/14 criteria on leadership capacity and 3/7 criteria on financial management capacity had significant improvements after the intervention (p < 0.001). The average score of most of these criteria increased from about 3 points at the baseline to 4 points after the intervention. However, financial management capacity is the skill group with the least improvement among the 5 skill groups evaluated, the highest criterion only reaching an average of 4.07 points; this requires the need to continue to prioritize training for this content in the coming time. Conclution: There has been an improvement in hospital treatment and care outcomes following a series of capacity building training courses for head nurses.